E-Service Quality and E-Loyalty in Online Travel Platforms: Evidence from East Indonesian Users - Muhammad Suriyadarman Rianse; Muhammad Fajar Salemaku; Najarudin (LP2M IAIN Palopo, 2026)
This study wants to find out how electronic service quality (e-servqual) affects electronic loyalty (e-loyalty) among Traveloka users in Kendari City, Indonesia. The study looks at how the quality of digital services offered by an online travel platform affects users' loyalty, especially their plans to use the site again and tell others about it. While prior research has extensively examined the correlation between service quality and client loyalty in e-commerce, empirical investigations concentrating on online travel platforms in emerging nations are still somewhat scarce. Specifically, research examining the influence of electronic service quality on user loyalty within online travel agents (OTAs) in Eastern Indonesia remains limited. This study adds to the body of research by looking at how the quality of e-services affects e-loyalty in the digital travel service environment. Methods: This study used a survey method and a quantitative explanatory approach. We got information from 100 people who had used the Traveloka app in Kendari City. We employed purposive sampling to get the data, and we used structured questionnaires to do so. We used SPSS software to look at the association between e-service quality and e-loyalty by using descriptive statistics and simple linear regression. Results: The findings demonstrate that e-service quality exerts a favorable and significant influence on e-loyalty among Traveloka users. This shows that customers are more likely to stick with the platform if it has better service, a more reliable system, is easier to use, and is safer for transactions. What it means: The results show how important it is to improve the quality of electronic services in order to keep customers coming back in the competitive online travel company operations. Implications: The results highlight the importance of improving electronic service quality in order to strengthen customer loyalty in the competitive online travel industry. Practically, the findings suggest that online travel platforms should continuously enhance system performance, usability, and security features to maintain long-term user engagement and loyalty.